If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-1x + 10) = 20 Reorder the terms: 4(10 + -1x) = 20 (10 * 4 + -1x * 4) = 20 (40 + -4x) = 20 Solving 40 + -4x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + -4x = 20 + -40 Combine like terms: 40 + -40 = 0 0 + -4x = 20 + -40 -4x = 20 + -40 Combine like terms: 20 + -40 = -20 -4x = -20 Divide each side by '-4'. x = 5 Simplifying x = 5
| 2x^4=54x | | 1/4(4-x)=10+2x | | -x+3=-8 | | 6k^2-35k+36=0 | | 7x+122=5x+412 | | -7-10=18+3x | | 10x+4=x^2-4 | | 2-5(2-x)=2 | | -5x-5=30 | | 9x^2-53x-70=0 | | 2(5+5x)=130 | | 3.1x+6.9x= | | 10x+4=x^2+4 | | 4n+5n+3(n+4)= | | 0.6x+0.27=1.35 | | 0=2x^2-200x+3200 | | 8x^2-89x+90=0 | | 6x-2=-20 | | 13-4(3x+5y)= | | 7(y-7)=6y-1 | | -3(-5x-2)=126 | | 6v^2+17v+10=0 | | -4x+1=-27 | | 6x+-9=27x+5 | | 7y=2y-16 | | 12x-15+3x+45=180 | | 0.40x+0.20(20)=0.20(42) | | 36-6x=6x+8(1-5x) | | 6x-9=27x+5 | | 3.1x+6.8x= | | 2(25+3a)=92 | | 6m^2+31m+28=0 |